Sweroside Alleviated Aconitine-Induced Cardiac Toxicity in H9c2 Cardiomyoblast Cell Line - Ma, Li-Qun; Yu, You; Chen, Hui; Li, Mei; Ihsan, Awais; Tong, Hai-Ying; Huang, Xian-Ju; Gao, Yue (Frontiers in Pharmacology, 2018)
Aconitine is the main bioactive ingredient of Aconitum plants, which are well-known botanical herbs in China. Aconitine is also notorious for its high cardiotoxicity, as it can induce life-threatening ventricular arrhythmias. Unfortunately, there are few effective antidotes to aconitine toxicity. This study aimed to evaluate the potent protective effects of the ingredients from V. baillonii on aconitine toxicity on H9c2 cell line. Cell viability was assessed by MTT. Intracellular Ca2+ concentration alteration and ROS generation were observed by confocal microscopy and flow cytometry, respectively. Cellular oxidative stress was analyzed by measuring MDA and SOD levels. Mitochondrial membrane potential (△Ψ) was determined using JC-1 kit. RT-PCR and Hoechst staining techniques were conducted to determine the levels of autophagy/apoptosis. The mRNA levels of dihydropyridine receptor (DHPR), ryanodine receptors (RyRs) and sarcoplasmic reticulum Ca2+-ATPase (SERCA) were measured by RT-PCR. We screened six components from V. baillonii, among which, sweroside exhibited the strongest protective effects on aconitine-induced cardiac toxicity. Sweroside suppressed the aconitine-induced mRNA expressions of NaV1.5 (encoded by SCN5A), RyR2 and DHPR, and reversed the aconitine-induced decrease in mRNA level of SERCA, thus preventing the aconitine-induced persistent intracellular Ca2+ accumulation and avoiding intracellular Ca2+ overload. We further found that sweroside restabilized the aconitine-disrupted mitochondrial membrane potential (△Ψ) and reversed the aconitine-induced increase in the mRNA levels of cell autophagy-related factors (Beclin-1, Caspase-3 and LC3-II) in H9c2 cells. Our results demonstrate that sweroside may protect cardiomyocytes from aconitine toxicity by maintaining intracellular Ca2+ homeostasis, restabilizing mitochondrial membrane potential (△Ψ) and avoiding cell autophagy/apoptosis.